Ambipolar Organic Tri‐Gate Transistor for Low‐Power Complementary Electronics. Issue 2 (17th November 2015) - Torricelli, Fabrizio; Ghittorelli, Matteo; Smits, Edsger C. P.; Roelofs, Christian W. S.; Janssen, René A. J.; Gelinck, Gerwin H.; Kovács‐Vajna, Zsolt M.; Cantatore, Eugenio
Abstract : Ambipolar transistors typically suffer from large off‐current inherently due to ambipolar conduction. Using a tri‐gate transistor it is shown that it is possible to electrostatically switch ambipolar polymer transistors from ambipolar to unipolar mode. In unipolar mode, symmetric characteristics with an on/off current ratio of larger than 10 5 are obtained. This enables easy integration into low‐power complementary logic and volatile electronic memories.